FERMION-BOSON CLASSIFICATION IN MICROCLUSTERS - Anagnostatos, G. S. (HNPS Advances in Nuclear Physics, 2020)
Mlcroclusters composed of atoms with non delocallzed odd number of valence electrons possess the usual magic numbers for fermions in a central potential and those with an even number of valence electrons possess the magic numbers for bosons coming from the packing of atoms in nested icosahedral or octahedral or tetrahedral shells. On the other hand, mlcroclusters composed of atoms with delocallzed valence electrons, either with an odd or with an even number of electrons, exhibit electronic magic numbers (according to the jelllum model) but also magic numbers coming from the (same, as above) packings of their bosonlc ion cores. Finally, through the present work, an alternative approach to study atomic nuclei as quantum clusters appears possible and promising.